2016
DOI: 10.1074/jbc.m115.703959
|View full text |Cite
|
Sign up to set email alerts
|

RhoC GTPase Is a Potent Regulator of Glutamine Metabolism and N-Acetylaspartate Production in Inflammatory Breast Cancer Cells

Abstract: Inflammatory breast cancer (IBC) is an extremely lethal cancer that rapidly metastasizes. Although the molecular attributes of IBC have been described, little is known about the underlying metabolic features of the disease. Using a variety of metabolic assays, including 13 C tracer experiments, we found that SUM149 cells, the primary in vitro model of IBC, exhibit metabolic abnormalities that distinguish them from other breast cancer cells, including elevated levels of N-acetylaspartate, a metabolite primarily… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 48 publications
0
41
0
Order By: Relevance
“…We then examined how the Rho-like family of Rho-GTPases impact mitochondrial fragmentation, based on their known role in regulating cytoskeletal dynamics. And, more specifically, our previous work found that inhibition of RhoC impairs the metabolic properties of inflammatory breast cancer cells 33 . Application of the MitoTracker strategy downstream of the metabolic flux assay revealed that RhoC deletion significantly increases the number of fragmented mitochondria in inflammatory breast cancer cells, which we hypothesize contributes to the depleted OCR levels ( Fig.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…We then examined how the Rho-like family of Rho-GTPases impact mitochondrial fragmentation, based on their known role in regulating cytoskeletal dynamics. And, more specifically, our previous work found that inhibition of RhoC impairs the metabolic properties of inflammatory breast cancer cells 33 . Application of the MitoTracker strategy downstream of the metabolic flux assay revealed that RhoC deletion significantly increases the number of fragmented mitochondria in inflammatory breast cancer cells, which we hypothesize contributes to the depleted OCR levels ( Fig.…”
Section: Discussionmentioning
confidence: 93%
“…The Rho-like family of Rho-GTPases have been well characterized for their participation in the progression of breast cancer 32,3436 and the alteration of metabolic phenotype 33 . Therefore, we next applied our imaging and analysis strategy to explore the potential for fragmented mitochondria in breast cancer cells that lack either the Rho-like family of Rho-GTPases RhoA or RhoC, via CRISPR/Cas9 knockout (WT, RhoA KO, RhoC KO) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The workflow of the experimental approach is outlined in Figure 7 and the metabolic network is illustrated in Figure 6. The network includes reactions involved in glycolysis and the tricarboxylic acid (TCA) cycle in breast cancer cell lines (Wynn et al, 2016). The input fluxes are glucose and glutamine, and the output fluxes are alanine, alpha-ketoglutarate, aspartate, glutamine, lactate, and oxaloacetate.…”
Section: Comparison Of Correction Methodsmentioning
confidence: 99%
“…RhoA and RhoC are highly homologous GTPases (approximately 92% amino acid identity) that have each been implicated in glutamine metabolism [5][6][7] . RhoA has been better characterized than RhoC, however several studies have demonstrated that they present distinct functions in cancer.…”
Section: Introductionmentioning
confidence: 99%